Carotid Arterial Stiffness and Hemodynamic Responses to Acute Cycling Intervention at Different Times during 12-Week Supervised Exercise Training Period. (16th July 2018) - Liu, Hai-Bin; Yuan, Wen-Xue; Wang, Qing-Yong; Wang, Yan-Xia; Cao, Hou-Wen; Xu, Jian; Qin, Kai-Rong
Abstract : This paper studied the alterations in arterial stiffness and hemodynamic responses during resting state and immediately following acute cycling intervention at different times across 12-week supervised exercise training. Twenty-six sedentary young males participated in the exercise training program at moderate intensity. Arterial stiffness and hemodynamic variables of the right common carotid artery were measured and computed during resting state and immediately following acute cycling intervention at weeks 0, 4, 8, and 12. Across the 12-week exercise training, carotid arterial stiffness was decreased at weeks 8 and 12 and hemodynamic variables were improved at week 12 during resting state. In response to acute cycling intervention, carotid arterial stiffness exhibited an acute increase foremost at 8 weeks, and arterial maximal and mean diameters showed acute decreases at weeks 0 and 4. Despite significant differences in arterial stiffness and hemodynamic variables between resting state and immediately after acute intervention for each time period, these differences presented a progressive decrease across the 12-week exercise training. In conclusion, long-term exercise training not only improved carotid arterial stiffness and hemodynamic alterations when at rest but also negated the acute responses of carotid arterial stiffness and hemodynamic variables to acute cycling intervention.